Efeito do processo de usinagem no comportamento de corrosão sob tensão do aço SAE 1020 - Lima, Michele Cravo de (Universidade Federal de São Carlos, 2021)
Corrosion is a natural phenomenon that causes a reduction in the life of components made with metallic and non-metallic materials. This process remains in constant research in order to be avoided by industries through detection techniques and anticorrosive methods. One type of high impact corrosion is stress corrosion cracking (CST), a phenomenon that occurs when a (susceptible) metal is exposed to an aggressive environment and, at the same time, it is tensioned, a very common situation in oil pipelines. Considering the importance of increasing the life of components by reducing the effects of corrosion and knowing that most parts produced are finished by material removal processes and these processes generate defects on the surfaces that can lead the component to premature failure, this research aims to understand the effect of machining on the life of a SAE 1020 steel subjected to CST. For this purpose, specimens of the aforementioned material were turned under different feed rates and exposed to an aggressive environment (NaOH solution), at a temperature of 55°C, and subjected to a fixed tensile load, according to ASTM G49- 85. In addition to the CST tests, specimens were made for corrosion tests by immersion in the same solution, in order to determine the effect of stress. The results obtained showed that the parts machined with higher feed values were more degraded, both in generalized corrosion and in CST. In the first case, alveolar corrosion on the surface was verified, while in the second, crack formation was noted.
Effect of the machining process on corrosion behavior under tension of SAE 1020 steel
Keywords: Materiais metálicos; Acabamento; Torneamento; Corrosão alveolar; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO